Oxygen-Generating Biomimetic Nano-Herb System for Synergistic Therapy & Pain Relief in Triple-Negative Breast Cancer via HIF-1α/VEGF Pathway - Cao DC; Liang Y; Guo Y; Wu DY; Wang NN; Li YM; Sun HF; Wang Q; Zhang X; Chi YL; Sun PP; Li YJ; et al. (International Journal of Nanomedicine)
Dian-Chao Cao,1– 3,* Yan Liang,1,4,* Yang Guo,1 Dong-Yang Wu,1 Na-Na Wang,1 Yan-Mei Li,5 Hong-Fang Sun,1 Qin Wang,1 Xia Zhang,1 Yong-Liang Chi,6 Pei-Pei Sun,4 You-Jie Li,1 Ran-Ran Wang,7 Ping-Yu Wang,1,8 Shu-Yang Xie,1– 3 Ning Xie9 1Department of Biochemistry and Molecular Biology, Binzhou Medical University, Yantai, Shandong, 264003, People’s Republic of China; 2Department of General Surgery, the second Medical College, Yantai Affiliated Hospital, Binzhou Medical University, Yantai, Shandong, 264003, People’s Republic of China; 3Shandong Laboratory of Advanced Materials and Green Manufacturing, Yantai, Shandong, 264000, People’s Republic of China; 4Department of Oncology, Binzhou Medical University Affiliated Hospital of Traditional Chinese Medicine, Binzhou, Shandong, 256600, People’s Republic of China; 5Department of Immune Rheumatism, Yantaishan Hospital, Yantai, Shandong, 264000, People’s Republic of China; 6Department of Anesthesiology, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, 250011, People’s Republic of China; 7Department of Rehabilitation Engineering, Institute of Rehabilitation Medicine, School of Rehabilitation Medicine, Binzhou Medical University, Yantai, Shandong, 264003, People’s Republic of China; 8Department of Epidemiology, Binzhou Medical University, Yantai, Shandong, 264003, People’s Republic of China; 9Department of Chest Surgery, Binzhou Medical University Affiliated Yantaishan Hospital, Yantai, Shandong, 264000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ning Xie, Department of Chest Surgery, Binzhou Medical University Affiliated Yantaishan Hospital, Yantai, Shandong, 264000, People’s Republic of China, Tel +86-0535-6913211, Fax +86 0535 6913163, Email sunnyvvv@163.com Shu-Yang Xie, Department of Biochemistry and Molecular Biology, Binzhou Medical University, Yantai, Shandong, 264003, People’s Republic of China, Tel +86 0535 6913211, Fax +86 0535 6913163, Email xieshuyang@bzmc.edu.cnPurpose: This study aims to develop an innovative delivery system, (Q+M/MnOx)@Clip, to enhance the bioavailability and therapeutic efficacy of quercetin both in tumor treatment and pain alleviation.Methods: The (Q+M/MnOx)@Clip system was evaluated to enhance the release of quercetin, investigate its ability to target cancer cells, alleviate tumor hypoxia, and improve the efficacy of chemodynamic therapy (CDT). Tumor hypoxia markers and immune response activation were assessed, along with the impact on pain relief biomarkers.Results: (Q+M/MnOx)@Clip successfully mitigated tumor hypoxia, facilitated controlled Q release, and enhanced CDT in vitro and in vivo. The system demonstrated a dual therapeutic effect: anti-tumor immunity and significant cancer pain relief by reducing HIF-1α and VEGF-A levels.Conclusion: The novel (Q+M/MnOx)@Clip system represents a promising advancement in nanomedicine, improving the bioavailability of quercetin and offering a more effective approach to cancer treatment by downregulation of HIF-1α and VEGF-A. This study demonstrates the potential for combining anti-tumor immunity with pain relief for triple-negative breast cancer therapy.Keywords: quercetin, pain relief, cancer immunotherapy, chemodynamic therapy, biomimetic, oxygen generation